A polycystin-2 (TRPP2) dimerization domain essential for the function of heteromeric polycystin complexes - Giamarchi, Aurélie (Nature Publishing Group, 2010)
Autosomal dominant polycystic kidney disease (ADPKD) is caused by mutations in two genes, PKD1 and PKD2, which encode polycystin-1 (PC1) and polycystin-2 (PC2), respectively. Earlier work has shown that PC1 and PC2 assemble into a polycystin complex implicated in kidney morphogenesis. PC2 also assembles into homomers of uncertain functional significance. However, little is known about the molecular mechanisms that direct polycystin complex assembly and specify its functions. We have identified a coiled coil in the C-terminus of PC2 that functions as a homodimerization domain essential for PC1 binding but not for its self-oligomerization. Dimerization-defective PC2 mutants were unable to reconstitute PC1/PC2 complexes either at the plasma membrane (PM) or at PM-endoplasmic reticulum (ER) junctions but could still function as ER Ca(2+)-release channels. Expression of dimerization-defective PC2 mutants in zebrafish resulted in a cystic phenotype but had lesser effects on organ laterality. We conclude that C-terminal dimerization of PC2 specifies the formation of polycystin complexes but not formation of ER-localized PC2 channels. Mutations that affect PC2 C-terminal homo- and heteromerization are the likely molecular basis of cyst formation in ADPKD.